Anti‐TNFα treatment in Crohn's disease: Impact on hepatic steatosis, gut‐derived hormones and metabolic status. (21st July 2021) - Manka, Paul; Sydor, Svenja; Wase, Nishikant; Best, Jan; Brandenburg, Malte; Hellbeck, Annika; Schänzer, Julia; Vilchez‐Vargas, Ramiro; Link, Alexander; Figge, Anja; Jähnert, Andreas; von Arnim, Ulrike; et al.
Abstract: Background and Aims: An association between Crohn's disease (CD) and hepatic steatosis has been reported. However, the underlying mechanisms of steatosis progression in CD are not clear. Among the most effective CD treatments are agents that inhibit Tumor‐Necrosis‐Factor (TNF) activity, yet it is unclear why anti‐TNFα agents would affect steatosis in CD. Recent studies suggest that microbiome can affect both, CD and steatosis pathogenesis. Therefore, we here analysed a potential relationship between anti‐TNF treatment and hepatic steatosis in CD, focusing on the gut‐liver axis. Methods: This cross‐sectional study evaluated patients with established CD, with and without anti‐TNFα treatment, analysing serum markers of liver injury, measurement of transient elastography, controlled attenuation parameter (CAP) and MRI for fat detection. Changes in lipid and metabolic profiles were assessed by serum and stool lipidomics and metabolimics. Additionally, we analysed gut microbiota composition and mediators of bile acid (BA) signalling via stool and serum analysis. Results: Patients on anti‐TNFα treatment had less hepatic steatosis as assessed by CAP and MRI. Serum FGF19 levels were significantly higher in patients on anti‐TNFα therapy and associate with reduced steatosis and increased bowel motility. Neutral lipids including triglycerides were reduced in the serum of patients on anti‐TNF treatment. Bacteria involved in BA metabolism and FGF19 regulation, including Firmicutes, showed group‐specific alterations with low levels in patients without anti‐TNFα treatment. Low abundance of Firmicutes was associated with higher triglyceride levels. Conclusions: Anti‐TNFα treatment is associated with reduced steatosis, lower triglyceride levels, alterations in FXR‐signalling (eg FGF19) and microbiota composition in CD.